Capital Budgeting in Small-Scale Industries - Yadav, Vinod Kumar (Indian Journal of Finance, 2013)
The decisions on capital expenditures are very important for every firm, whether it is a small-scale industry or a large firm, because their impact is more or less permanent on the well-being and economic health of the enterprise. Capital budgeting may be more important to the smaller firms than it is to their larger counterparts because of the lack of the diversification in smaller firms. The main objective of this study is to examine the decision-making process followed by small-scale industries to evaluate the purchase of major fixed assets. For this purpose, relevant data were collected through a questionnaire, interviews and personal observations by undertaking an intensive case study of 400 small-scale industries of Haryana. This study found that in the small-scale industries, only large units, in the true sense of capital budgeting, prepared capital budgets for taking long-term capital investment decisions, and comprised of only 12.5% units of the total small-scale industries. In the small-scale industries, the traditional methods of capital budgeting- PBP and ARR -were used for evaluation of projects. It was found that in the small-scale industries, capital budgets were prepared by a committee comprising of both - the owner and the experts. It was also observed that an important aspect of capital budgeting - post audit - was used by only 6% of the sample units.